Monoclonal Antibodies to Conformational Epitopes of the Surface Glycoprotein of Caprine Arthritis-Encephalitis Virus: Potential Application to Competitive-Inhibition Enzyme-Linked Immunosorbent Assay for Detecting Antibodies in Goat Sera - Özyörük, Fuat (American Society for Microbiology, 2001)
Four immunoglobulin G1 monoclonal antibodies (MAbs) to the gp135 surface envelope glycoprotein (SU) of the 79–63 isolate of caprine arthritis-encephalitis virus (CAEV), referred to as CAEV-63, were characterized and evaluated for their ability to compete with antibody from CAEV-infected goats. Three murine MAbs (MAbs GPB16A, 29A, and 74A) and one caprine MAb (MAb F7-299) were examined. All MAbs reacted in nitrocellulose dot blots with native CAEV-63 SU purified by MAb F7-299 affinity chromatography, whereas none reacted with denatured and reduced SU. All MAbs reacted in Western blots with purified CAEV-63 SU or the SU component of whole-virus lysate following denaturation in the absence of reducing agent, indicating that intramolecular disulfide bonding was essential for epitope integrity. Peptide-N-glycosidase F digestion of SU abolished the reactivities of MAbs 74A and F7-299, whereas treatment of SU with N-acetylneuraminate glycohydrolase (sialidase A) under nonreducing conditions enhanced the reactivities of all MAbs as well as polyclonal goat sera. MAbs 29A and F7-299 were cross-reactive with the SU of an independent strain of CAEV (CAEV-Co). By enzyme-linked immunosorbent assay (ELISA), the reactivities of horseradish peroxidase (HRP)-conjugated MAbs 16A and 29A with homologous CAEV-63 SU were <10% of that of HRP-conjugated MAb 74A. The reactivity of HRP-conjugated MAb 74A was blocked by sera from goats immunized with CAEV-63 SU or infected with CAEV-63. The reactivity of MAb 74A was also blocked by sera from goats infected with a CAEV-Co molecular clone, although MAb 74A did not react with CAEV-Co SU in Western blots. Thus, goats infected with either CAEV-63 or CAEV-Co make antibodies that inhibit binding of MAb 74A to CAEV-63 SU. A competitive-inhibition ELISA based on displacement of MAb 74A reactivity has potential applicability for the serologic diagnosis of CAEV infection.